Comparison of Fixation Techniques of 3D-Woven Poly(ϵ-Caprolactone) Scaffolds for Cartilage Repair in a Weightbearing Porcine Large Animal Model - Friedman, James M. (Cartilage, 2017)
OBJECTIVE: To test different fixation methods of a 3-dimensionally woven poly(ϵ-caprolactone) (PCL) scaffold within chondral defects of a weightbearing large animal model. METHODS: Full thickness chondral defects were made in the femoral condyles of 15 adult male Yucatan mini-pigs. Two surgical approaches were compared including total arthrotomy (traditional) and a retinaculum-sparing, minimally invasive surgery (MIS) approach. Following microfracture (MFX), scaffolds were placed without fixation or were fixed with fibrin glue, suture, or subchondral anchor. Experimental endpoints were between 1 and 6 weeks. Micro–computed tomography and histology were used to assess samples. RESULTS: The MIS approach was superior as the traditional approach caused medial condyle cartilage wear. One of 13 (7.7%) of scaffolds without fixation, 4 of 11 (36.3%) fibrin scaffolds, 1 of 4 (25%) of sutured scaffolds, and 9 of 9 (100%) of anchor-fixed scaffolds remained in place. Histology demonstrated tissue filling with some overgrowth of PCL scaffolds. CONCLUSIONS: Of the methods tested, the MIS approach coupled with subchondral anchor fixation provided the best scaffold retention in a mini-pig chondral defect model. This finding has implications for fixation strategies in future animal studies and potential future human use.